Electricity market design for generator revenue sufficiency with increased variable generation. (December 2015) - Levin, Todd; Botterud, Audun
Abstract: We present a computationally efficient mixed-integer program (MIP) that determines optimal generator expansion decisions, and hourly unit commitment and dispatch in a power system. The impact of increasing wind power capacity on the optimal generation mix and generator profitability is analyzed for a test case that approximates the electricity market in Texas (ERCOT). We analyze three market policies that may support resource adequacy: Operating Reserve Demand Curves (ORDC), Fixed Reserve Scarcity Prices (FRSP) and fixed capacity payments (CP). Optimal expansion plans are comparable between the ORDC and FRSP implementations, while capacity payments may result in additional new capacity. The FRSP policy leads to frequent reserves scarcity events and corresponding price spikes, while the ORDC implementation results in more continuous energy prices. Average energy prices decrease with increasing wind penetration under all policies, as do revenues for baseload and wind generators. Intermediate and peak load plants benefit from higher reserve prices and are less exposed to reduced energy prices. All else equal, an ORDC approach may be preferred to FRSP as it results in similar expansion and revenues with less extreme energy prices. A fixed CP leads to additional new flexible NGCT units, but lower profits for other technologies. Highlights: We model three market policies for resource adequacy in power systems with wind. Unit expansion is comparable between ORDCs and fixed reserves scarcity pricing. ORDCs lead to a more continuous spectrum of energy prices and fewer price spikes. Revenues for baseload generators generally decrease with increasing wind penetration. Capacity payments lead to additional NGCT units and lower energy prices.